GENDER DIFFERENCES IN RISK TOLERANCE, HERDING BEHAVIOR AND OVERCONFIDENCE AMONG STOCK INVESTORS IN ACEH - Zaida Rizqi Zainul; Irma Suryani (Jurnal Bisnis Manajemen, 2022)
ehavioural Finance is starting to be interesting to study because it plays a role in making a person's decision to invest. Investors do not only use estimates of the prospects for investment instruments, but psychological factors also determine investment decisions. The purpose of this study was to determine the extent to which there are gender differences in risk tolerance, overconfidence and investment behavior among stock investors in Aceh. The data used in this research is primary data. Data collection techniques through questionnaires. The population in this study are investors who are domiciled in Aceh Province with a total sample of 386 respondents consisting of 193 male and female respondents. The analytical method used is the Man Whitney U Test. The results showed that: 1) There is a difference in risk tolerance between male and female investors in Aceh, 2) There is no difference in overconfidence between male and female investors in Aceh 3) There is a difference in herding behavior between male and female investors in Aceh. Advances in information technology, education levels, knowledge have made gender differences no longer a barrier for investors in Aceh to feel more confident and courageous in making investment decisions. This study is expected to enrich the literature on investor behavior based on gender and increase the number of capital market investors in Aceh through an investor behavior approach.